2018
DOI: 10.1039/c8ra01709c
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonium acidic ionic liquid: an efficient and recyclable homogeneous catalyst for the synthesis of 2-arylbenzoxazoles, 2-arylbenzimidazoles, and 2-arylbenzothiazoles

Abstract: A highly efficient and green strategy for the synthesis of 2-arylbenzoxazoles, 2-arylbenzimidazoles, and 2-arylbenzothiazoles catalyzed by phosphonium acidic ionic liquid has been developed via the condensation of o-aminophenol, o-phenylenediamines, and o-aminothiophenol, respectively, with aldehydes. The reaction has a good yield, the broad substrate scope, and mild condition. Triphenyl(butyl-3-sulphonyl) phosphonium toluenesulfonate catalyst was easily obtained from cheap and available starting materials thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…Nguyen et al 63 reported the phosphonium acidic ionic liquid [triphenyl(butyl-3-sulfonyl) phosphonium toluene sulfonate catalyzed synthesis of 2-aryl benzoxazole ( 3 ) from 2-aminophenol ( 1 ) and aryl aldehydes ( 2 ) at 100 °C under solvent-free conditions. The authors prepared 35 derivatives with 65–96% yield.…”
Section: Synthesis Of Benzoxazole Derivativesmentioning
confidence: 99%
“…Nguyen et al 63 reported the phosphonium acidic ionic liquid [triphenyl(butyl-3-sulfonyl) phosphonium toluene sulfonate catalyzed synthesis of 2-aryl benzoxazole ( 3 ) from 2-aminophenol ( 1 ) and aryl aldehydes ( 2 ) at 100 °C under solvent-free conditions. The authors prepared 35 derivatives with 65–96% yield.…”
Section: Synthesis Of Benzoxazole Derivativesmentioning
confidence: 99%
“…Ngoài ra, một số loại chất màu nhạy quang (dye, là thành phần chủ yếu trong pin mặt trời nhạy quang) đã được điều chế từ cơ cấu khung benzoxazole [5][6][7] . Có nhiều phương pháp tổng hợp các dẫn xuất benzoxazole đã được nghiên cứu như aryl hóa benzoxazole với các aldehyde hương phương 8,9 , đóng vòng các dẫn xuất của các hợp chất 2-nitrophenol hay 2-aminophenol với các loại chất nền khác nhau như halobenzene 10,11 , alcol 12 , aldehyde [13][14][15] , ketone 16,17 , carboxylic acid 18 , orthoester 19 , acid chloride 20 , isocyanide 21 , oxime amide 22 , diphenylacety-lene 23 , phenyl-boronic acid 24…”
Section: Giới Thiệuunclassified
“…[39][40][41][42][43][44] Traditional methods for obtaining 2substituded benzoxazoles, such as the condensation of 2aminophenol and carboxylic acid 45 or the oxidative cyclization of phenolic Schiff bases, 46 have drawbacks related to the use of strong acids, toxic reagents, harsh reaction conditions, and the generation of dangerous peroxides and salt waste. [47][48][49][50][51] In the last decade, many methods have been proposed for the optimization of 2-arylbenzoxazoles synthesis featuring improvements in terms of reaction time, waste generation, milder temperature or pressure, avoidance of dangerous compounds, [52][53][54][55][56][57] but none of them have thus far demonstrated the reduction of the environmental impacts in a comprehensive and analytical manner.…”
Section: Introductionmentioning
confidence: 99%